Are interest rates alone enough to understand stock returns in the Islamic Republic of Pakistan?. (9th August 2019) - Badshah, Imtiaz; Ahmad, Maaheen; Jaber, Khalifa Hmood
The purpose of this paper is to understand the volatility of interest rates and the relationship between interest rates and stock returns under three political regimes in Pakistan. The wealth of literature discussing the volatility of interest rates and stock returns provided the theoretical basis for this inquiry. This research is therefore deductive in nature and situated within a positivist philosophical paradigm. This research is unique in its methodological approach, dividing the study period into three short periods (2002-2008, 2008-2013 and 2013-2016) based upon the political regimes in the country, which leads to interesting findings. Regression analyses are used to investigate the relationship between interest rates and stock returns. This research contributes additional insights into the relationship between interest rates and stock returns in Pakistan. Factors, such as political regimes, the relationship between political regimes and international investors and organisations, and the law and order situation etc play greater role.